Perfil e visão de trabalho expressa por professores eventuais de escolas de uma diretoria de ensino da Rede Estadual de São Paulo - Oliveira, Lorena Rodrigues de (2010)
The temporary teachers working in schools in state of Sao Paulo as a means of remedying the problem of shortages of professors, replacing any absences. There are about 17,000 teachers working as a eventual teacher, which can be considered on duty at school, without any guarantee and employment stability. The main objective of this research is to draw a profile of teachers in any Board of Education Caieiras, metropolitan region of São Paulo state and identify the vision they express about their work and their situation professional. It's knowing who they are, as perceive their work and their relationship with the organization school. For this, a search was conducted qualitative, whose instruments for collecting data, in 2009, were the questionnaires, semi-structured interviews with teachers and any document analysis. The research has as reference, mainly the work of Gimeno Sacristán (1999), Vorraber (1995) and Huberman (1995). Results presented in charts and tables suggest that interviewed teachers are mostly young teachers with little training time, are formed predominantly in private institutions. In relation to the vision that express about their work demonstrate that they feel devalued and exhibit a difficult relationship with other teachers in schools and working with students